2019
DOI: 10.3390/jcm8091332
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-Lowering Drugs for Type 2 Diabetes Mellitus and Metabolic Syndrome—Strategies for In Vivo Administration: Part-II

Abstract: Diabetes is a complex disease characterized by hyperglycemia, together with polyuria, polydipsia, and polyphagia. While Type 1 diabetes mellitus (T1DM) results from genetic, environmental, or immune dysfunction factors leading to pancreatic β-cell destruction depriving the organism from endogenous insulin, Type 2 diabetes mellitus (T2DM) is characterized by peripheral insulin resistance. Depending on the type of diabetes mellitus and drug mechanism to study, the animal model should be carefully selected among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 85 publications
1
29
0
Order By: Relevance
“…The epidemic metabolic disorder, diabetes mellitus (DM) is characterized by high blood glucose where the patient cannot produce adequate insulin, or body cells do not respond to glucose produced by β-cells in the pancreas. Many people have diabetes all over the world [1][2][3], and the number is increasing at an alarming rate. According to the World Health Organization, diabetes causes 1.5 million deaths each year worldwide, being one of the most recurrent cause of mortality in developed countries [2].…”
Section: Introductionmentioning
confidence: 99%
“…The epidemic metabolic disorder, diabetes mellitus (DM) is characterized by high blood glucose where the patient cannot produce adequate insulin, or body cells do not respond to glucose produced by β-cells in the pancreas. Many people have diabetes all over the world [1][2][3], and the number is increasing at an alarming rate. According to the World Health Organization, diabetes causes 1.5 million deaths each year worldwide, being one of the most recurrent cause of mortality in developed countries [2].…”
Section: Introductionmentioning
confidence: 99%
“…Nanonutraceutics could be an important tool useful among the strategies adopted in managing health conditions, particularly tailored to patients who are not eligible for a conventional pharmacological therapy. Studies on follow up, use, and compliance of pharmaceuticals reported in the area [98][99][100][101], as well as communication strategies and assessment [102], should be extended also to nutraceuticals and carried out in view of exploiting the field to different health conditions, e.g., the ones clustered in the so-called "metabolic syndrome", which includes conditions ranging from obesity to dysmetabolism [103][104][105]. These latter are often related to the food intake/dietary habits of each person.…”
Section: From Nanopharmaceutics To Nanonutraceutics: a Bet For The Fumentioning
confidence: 99%
“…The name of this disease is derived from a Greek word meaning "going through" and a Latin word for "honey" or "sweet" [1] and is characterized by the production of a large amount of urine with a honey-like taste [2]. DM is a metabolic disorder characterized by chronic hyperglycemia together with disturbances in the metabolism of carbohydrates, proteins and fat, which in general results from an insulin availability and need imbalance [1,[3][4][5]. Nowadays, the number of people suffering from DM and its complications is increasing, in part due to the current worldwide lifestyle: Sedentary lifestyle, high-fat diet, obesity and longer life span [6].…”
Section: Introductionmentioning
confidence: 99%